WALKER, Callum. An Eye-Tracking Study of Equivalent Effect in Translation: The Reader Experience of Literary Style. London, Palgrave MacMillan, 2021, 414 pp., ISBN 978-3-030-55769-0. - Jiang, Qihang (Hikma, 2022)
.